Implementation of IEEE 802.11e block acknowledgement policies based on the buffer size - Cabral, Orlando (2008)
Optimization of IEEE 802.11e MAC protocol performance is done by modifying several parameters left open in the standard, like buffer size and acknowledgement policies. By using the developed event-driven simulator, results were extracted with single and multi-service. With only a single service, higher values for the goodput are obtained for video and background (BK) traffics in comparison with the voice (VO) application. Besides, the number of supported user is higher for voice. With mixtures of traffic, when the number of station is small the goodput is lower for VO. However, for higher number of station, the lowest values for the goodput occur for background traffic. By using the Block Acknowledgement (ACK) procedure, for video and BK traffics, the capacity is improved when the number of station is equal or higher than 16 and 12, respectively. From a detailed analysis of the video application, a reduction of more than 40% was achieved in the delay. However, a clear trend is not identified for the optimum block size.